The Negative Impact of Broken Home Children in the Increase in Criminal Cases that Occur in Society in terms of Analysis of Islamic Family Law - Gafar Efendi; Jainuddin Jainuddin; Muh. Yunan Putra (Publikasi Indonesia, 2024)
This study will examine the impact of broken home families on children's behaviour. The effect of a broken home family condition can be analysed by observing a person's patterns and attitudes in daily activities. The observation procedure used is library research, using sources such as journals, books, and e-books relevant to this article's topic. In the analysis process, data is reviewed through the stages of review, sorting, grouping, and categorising to understand the impact of broken home families on children in increasing criminal cases in the community. The results showed that there are impacts of broken home families, including psychological effects that affect children's social life, children's knowledge of the criminal world, and spiritual effects that affect their religious behaviour.